The art of performance - Glusberg, Jorge; New York University, Department of art and art education, New York (New York : ICASA (International Center for Advanced Studies in Art) New York, 1986)
Agnetti, Vincenzo ; Bodanza, Gaetano K. ; Bonora, Lola ; Breakwell, Ian ; Calzolari, Pierpaolo ; Chiari, Giuseppe ; Clareboudt, Jean ; Efrat, Benni ; Export, Valie ; Fischer, Hervé ; Gerz, Jochen ; Haxton, David ; Joubert, Bernard ; Journiac, Michel ; Kahlen, Wolf ; Kubisch, Christina ; Kubota, Shigeko ; Levine, Les ; Lublin, Léa ; Maler, Leopoldo ; Marangoni, Federica ; Minkoff, Gérald ; Minujin, Marta ; Nitsch, Hermann ; Oppenheim, Dennis ; Orlan ; Otth, Jean ; Paik, Nam June ; Pane, Gina ; Peña, Rolando ; Pettena, Gianni ; Plessi, Fabrizio ; Schult, HA ; Sharp, Willoughby ; Todosijevic, Rasa Dragoljub ; Toma, Kathy ; Viola, Bill ; Yamaguchi, Katsuhiro
Engels
boek